Pengaruh Penggunaan Gadget dan Pola Asuh Islami terhadap Mental Spiritual Siswa - Ahmad Solehudin; Benny Prasetiya; Heri Rifhan Halili (Universitas Muhammadiyah Enrekang, 2021)
The author conducted this study with the aim the 2 independent variables, namely the Gadget as X1 and Islamic Parent as X2, on the 1 independent variable, namely the Mental Spirit as Y. The study was conducted using a quantitative method that collected data through the figures from the results of the questionnaire survey distributed via google form. The object of the research is the students of SMP Islamic Permata, Probolinggo City. The results showed that the Gadget (X1) and Islamic Parent (X2) had an effect of 5,5% on the Mental Spirit (Y).